A multi-country study of the associations between HIV vulnerability status, perception of COVID-19 related stigma and post-traumatic stress symptoms during the first wave of the pandemic - Folayan Morenike Oluwatoyin; Abeldaño Zuñiga Roberto Ariel; Virtanen Jorma I.; Ellakany Passent; Al-Tammemi Ala’a B.; Quadri Mir Faeq Ali; Jafer Mohammed; Ara Eshrat; Ayanore Martin Amogre; Gaffar Balgis; Aly Nourhan M.; Idigbe Ifeoma; et al. (BMC, 2025)
Background: This study investigated the associations between COVID-19 related stigma and post-traumatic stress symptoms (PTSS); and the associations between PTSS and COVID-19 related stigma, HIV status, COVID-19 status and key HIV population status.
Methods: This was a secondary analysis of data of 12,355 study participants generated through an online survey that recruited adults from 152 countries between July and December 2020. The dependent variables were COVID-19-related stigma and PTSS. The independent variables were HIV status (positive/negative), transaction sex (yes/no), use of psychoactive drugs (yes/no), and vulnerability status (transaction sex workers, people who use psychoactive drugs, living with HIV, and COVID-19 status). The confounding variables were age, sex at birth (male/female), level of education, sexual minority individuals (yes/no) and country income level. Multivariable logistic regression analyses were conducted to determine associations between the dependent and independent variables after adjusting for confounders.
Results: There were 835 (6.8%) participants who experienced COVID-19 related stigma during the pandemic and 3,824 (31.0%) participants reported PTSS. Respondents who were living with HIV (AOR: 1.979; 95%CI: 1.522-2.573), tested positive for COVID-19 (AOR: 3.369; 95%CI: 2.692-4.217), engaged in transactional sex (AOR: 1.428; 95%CI: 1.060-1.922) and used psychoactive drugs (AOR: 1.364; 95%CI: 1.053-1.767) had significantly higher odds of experiencing COVID-19 related stigma. Individuals with vulnerability status (AOR:4.610; 95%CI: 1.590-13.368) and who experienced COVID-19 related stigma (AOR: 2.218; 95%CI: 1.920-2.561) had significantly higher odds of PTSS.
Conclusion: Individuals with vulnerability status may be at increased risk for COVID-19 related stigma. Key and vulnerable populations who were living with HIV and who experienced stigma may be at a higher risk of experiencing PTSS. Populations at risk for PTSS should be routinely screened and provided adequate support when they contract COVID-19 to reduce the risk for poor mental health during COVID-19 outbreaks and during future health crisis with similar magnitude as the COVID-19 pandemic.